2003
DOI: 10.1076/ceyr.27.2.111.15949
|View full text |Cite
|
Sign up to set email alerts
|

Neural network approach to classify infective keratitis

Abstract: ANN has the potential to help clinicians classify corneal ulcers more accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…and slit lamp examination findings (including the elevation and texture of corneal infiltrates). [39][40][41][42] In much the same way that an expert clinician typically gathers information from multiple sources before formulating a diagnosis, predictive models for identifying the underlying cause of infection will likely benefit from accessing this additional contextual information in addition to imaging data. These models may also benefit from adopting a Bayesian decision framework accounting for the pre-test probability of different infectious agents based on local epidemiology, which demonstrates marked geographic variability.…”
Section: Discussionmentioning
confidence: 99%
“…and slit lamp examination findings (including the elevation and texture of corneal infiltrates). [39][40][41][42] In much the same way that an expert clinician typically gathers information from multiple sources before formulating a diagnosis, predictive models for identifying the underlying cause of infection will likely benefit from accessing this additional contextual information in addition to imaging data. These models may also benefit from adopting a Bayesian decision framework accounting for the pre-test probability of different infectious agents based on local epidemiology, which demonstrates marked geographic variability.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to diagnose FK with corneal photographs using DL-based machine learning techniques. Saini et al used the basic neural network structure to classify infective keratitis 26 . Their input consists of 40 variables on patients’ history and lab data for training and testing.…”
Section: Discussionmentioning
confidence: 99%
“…In order to decrease the need of diagnostic test and to simplify the diagnosis of patients with PIK the use of artificial neural networks (ANN) may have a role in the future. As described by Saini et al, 27 the ANN are associative self-learning techniques with the ability to identify multidimensional relationships and perform pattern recognition in nonlineal domains. Saini et al demonstrated that with the use of ANN they were able to correctly identify the category (fungal vs bacterial) in 39 of 44 cases of infectious keratitis.…”
Section: Case Nomentioning
confidence: 99%